(untitled) (Vietnam Journal of Community Medicine, 2025)
Herpes Simplex Virus Type 1 (HSV-1) encephalitis is a common cause of encephalitis worldwide [1]. The typical clinical symptoms include sudden onset, fever, headache, seizures, focal neurological signs, and impaired consciousness. The herpes virus invades the central nervous system, causing necrosis of brain parenchyma accompanied by hemorrhage [2]. Cerebral hemorrhage is extremely rare in the course of herpes simplex encephalitis. Additionally, cerebral hemorrhage complicates the progression of HSV encephalitis. Here, we report a case of a previously healthy male patient with HSV-1 who initially presented with cerebral hemorrhage.